Genome-wide gene-environment analyses of major depressive disorder and reported lifetime traumatic experiences in UK Biobank - Coleman, Jonathan R I; Peyrot, Wouter J; Purves, Kirstin L; Davis, Katrina A S; Rayner, Christopher; Choi, Shing Wan; Hübel, Christopher; Gaspar, Héléna A; Kan, Carol; Van der Auwera, Sandra; Adams, Mark James; Lyall, Donald M; et al. (Molecular psychiatry, 2020)
Depression is more frequent among individuals exposed to traumatic events. Both trauma exposure and depression are heritable. However, the relationship between these traits, including the role of genetic risk factors, is complex and poorly understood. When modelling trauma exposure as an environmental influence on depression, both gene-environment correlations and gene-environment interactions have been observed. The UK Biobank concurrently assessed Major Depressive Disorder (MDD) and self-reported lifetime exposure to traumatic events in 126,522 genotyped individuals of European ancestry. We contrasted genetic influences on MDD stratified by reported trauma exposure (final sample size range: 24,094-92,957). The SNP-based heritability of MDD with reported trauma exposure (24%) was greater than MDD without reported trauma exposure (12%). Simulations showed that this is not confounded by the strong, positive genetic correlation observed between MDD and reported trauma exposure. We also observed that the genetic correlation between MDD and waist circumference was only significant in individuals reporting trauma exposure (r = 0.24, p = 1.8 × 10 versus r = -0.05, p = 0.39 in individuals not reporting trauma exposure, difference p = 2.3 × 10 ). Our results suggest that the genetic contribution to MDD is greater when reported trauma is present, and that a complex relationship exists between reported trauma exposure, body composition, and MDD.